PERANCANGAN SISTEM INFORMASI PENDAFTARAN KELAS ONLINE SMARTPHONE PHOTOGRAPHY BERBASIS WEB (STUDI KASUS: MOTRET BARENG JD) - Adilah Nuur Hudaa (2021)
Online classes are learning supported by the internet network with connectivity, accessibility, flexibility, and the ability to provide a variety of interactions in the learning process. In its implementation, online classes can be applied using electronic devices such as laptops, smartphones, tablets, and so on. Motret Bareng JD is a program engaged in photography by opening an online smartphone photography class consisting of 13 class categories. In the implementation of registration activities are still done manually where data reporting is still recorded using paper media that can allow some obstacles, such as missing, damaged, and admins incorrectly inputting registrant data. Therefore, an information system is needed that can help the online class participant registration process. With the online class registration information system based on the website is expected to help facilitate admins in the registration process, such as data processing, fast and precise information delivery, and reporting can be managed quickly. The methods used are waterfall and PIECES methods. The results of this study are web-based online class registration information system at web-based Motret Bareng JD.